Research on design of permanent inter-satellite-links in satellite networks - WANG Zhen-yong; WANG Ping; GU Xue-mai; GUO Qing (Tongxin xuebao)
Based on constellation designation,conditions of permanent inter-satellite-links were analyzed in order to solve problems of continual handoff caused by relative movements of satellites in different orbits in satellite networks.A scheme to design constellations with permanent inter-satellite-links was proposed,and conditions to maintain in-ter-satellite-links were analyzed.By simulations,results are shown and examples are introduced for verification.